Nuclear Imaging of Post-infarction Inflammation in Ischemic Cardiac Diseases - New Radiotracers for Potential Clinical Applications - Krenning, Boudewijn J.; der Heiden, Kim v.; Duncker, Dirk J.; de Jong, Marion; Bernsen, Monique R. (Current Radiopharmaceuticals, 2021)
Acute myocardial infarction is one of the leading causes of death in the western world. Despite major improvements in myocardial reperfusion with sophisticated percutaneous coronary intervention technologies and new antithrombotic agents, there is still no effective therapy for preventing post- infarction myocardial injury and remodeling. Death of cardiomyocytes following ischemia results in “danger signals” that elicit an inflammatory reaction to remove cell debris and form scar tissue. Optimal healing of the damaged myocardial tissue requires a coordinated cellular response for sufficient wound healing and scar formation. However, if this inflammatory reaction is overactive or incompletely resolved, adverse left ventricular remodeling and heart failure may occur. Treatment aimed at the modulation of the post-MI inflammatory response has been widely pursued and investigated. Although improved infarct healing was shown in many experimental preclinical studies, to date, clinical trials using anti-inflammatory treatment strategies have been far less successful. Clearly, a need exists for predicting and selecting patients at risk and selecting the most appropriate therapy for individual patients. To this end, imaging of the post-MI response has been a topic of significant interest. In this review, we first discuss the clinical complications resulting from myocardial inflammation following AMI and the need for non-invasive imaging techniques using radiolabeled tracers. We then discuss the inflammatory reaction cascade following acute myocardial infarction, the inflammatory reaction cascade following acute myocardial infarction focusing on inflammatory cell types involved herein, and potential imaging targets for identifying these cells during the inflammatory process. In addition, we discuss specific characteristics and limitations of various preclinical animal models for ischemic heart disease since they are crucial in the development and evaluation of the imaging techniques. Finally, we discuss the need for non-invasive imaging approaches using radiolabeled tracers.
Keywords: inflammatory cell